Old Code Subject Files I
The series contains mostly microfilmed clippings from Czech, Slovak and foreign newspapers and revues. Includes extensive information related to agriculture, armed forces, political parties (large section on the Communist Party), opposition, economy, culture, industry, state apparatus and police.